2022
DOI: 10.3390/ijms232314994
|View full text |Cite
|
Sign up to set email alerts
|

Xylanase Inhibitors: Defense Players in Plant Immunity with Implications in Agro-Industrial Processing

Abstract: Xylanase inhibitors (XIs) are plant cell wall proteins largely distributed in monocots that inhibit the hemicellulose degrading activity of microbial xylanases. XIs have been classified into three classes with different structures and inhibition specificities, namely Triticum aestivum xylanase inhibitors (TAXI), xylanase inhibitor proteins (XIP), and thaumatin-like xylanase inhibitors (TLXI). Their involvement in plant defense has been established by several reports. Additionally, these inhibitors have conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 122 publications
2
8
0
Order By: Relevance
“…Here, we identified a xylanase inhibitor protein, OsHI‐XIP, that was induced in response to the MoXYL1 expression. A recent study demonstrated a complex model of the Triticum aestivum xylanase inhibitors (TAXI)‐BcXyn11, showing the binding of the 25‐residue peptide containing two conserved residues YGWT and YYIV with TAXI (Tundo et al, 2022). A previous study emphasized the role of rice chitinase‐like protein (OsCLP), which shares significant similarities with other plant TAXI‐type XIPs (Wu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we identified a xylanase inhibitor protein, OsHI‐XIP, that was induced in response to the MoXYL1 expression. A recent study demonstrated a complex model of the Triticum aestivum xylanase inhibitors (TAXI)‐BcXyn11, showing the binding of the 25‐residue peptide containing two conserved residues YGWT and YYIV with TAXI (Tundo et al, 2022). A previous study emphasized the role of rice chitinase‐like protein (OsCLP), which shares significant similarities with other plant TAXI‐type XIPs (Wu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…SUN et al [23], xylanase inhibitors (XIs) are plant cell wall proteins found mostly in monocots that limit microbial xylanases' hemicellulose degrading ability. Silvio Tundo et al [24]. The GSE34445 and GSE59723 data sets shared 4 genes (WRKY45, Cht2, WRKY, and ccd1), and the GSE31760 and GSE59723 shared 2 genes (TaAOS and tamdr1).…”
Section: Identification Of Degsmentioning
confidence: 99%
“…During an invasion by pathogenic fungi such as F. graminearum , these fungi secrete xylanases [ 10 ], which break down xylans, compromising the wheat cell wall integrity and facilitating further fungal invasion and spread [ 11 , 12 ]. Xylanase inhibitors (XIs) in wheat serve the critical function of neutralizing and inhibiting these exogenous xylanases [ 13 ]. In wheat, three distinct types of XIs have been identified based on their structural characteristics, namely thaumatin-like xylanase inhibitor (TLXI) type inhibitors [ 14 ], Triticum aestivum xylanase inhibitor (TAXI) [ 15 ] and xylanase inhibiting protein (XIP) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Each type of XI possesses unique domains that aid in their identification. TLXI shares significant homology with thaumatin-like proteins complicating the precise identification of TLXI family members [ 13 , 17 ]. For TAXI classification, both the xylanase inhibitor N-terminal and the Xylanase inhibitor C-terminal are used [ 18 ], whereas for XIP classification the glycoside hydrolase family 18 (GH18) is used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation